THE INFLUENCE OF ORGANIZATIONAL CULTURE, LEADERSHIP AND COMPENSATION ON ORGANIZATIONAL COMMITMENT - Warid, Agus (Indonesian Journal Of Business And Economics, 2023)
ABSTRACTThis study aims to determine the effect of organizational culture, leadershipand compensation on organizational commitment High organizationalcommitment is needed in an organization, because the creation of highcommitment will affect the professional work situation. Therefore, the factorsthat influence organizational commitment need to be well understood. Thisresearch uses a quantitative and descriptive technique approach with the surveymethod as the research design. Primary data was collected throughquestionnaires through Gform distributed to respondents consisting ofemployees of the Kuningan Regency Pol PP Office. The research sample wastaken using the sampling technique with the slovin method, The number ofrespondents who participated in this study were 57 respondents. The resultsshowed that organizational culture has a positive effect on organizationalcommitment, leadership has a positive effect on organizational commitmentand compensation has a positive effect on organizational commitment. As wellas organizational culture, leadership and compensation simultaneously affectorganizational commitment.